Analysis of financial performance of the commercial banks in the Gulf Cooperation Council (GCC) countries - Al-Yousfi, Abdulazeez Yousef Hazzaa Saif (2017)
Research on performance of banks in the Gulf Cooperation Council (GCC) countries is very limited despite being one of the key global banking markets, main suppliers of oil around the globe, and economies that attract significant foreign direct investment (FDI). Hence, this study provides new insight on bank performance using bank-specific, macroeconomic, and financial structure indicators. Using the generalized method of moments dynamic model estimation, this study analyses the perfom1ance of banks in GCC countries over the period from 2000-2015. This study finds that the perfom1ance of foreign banks is better than that of domestic banks and the performance of listed banks is better than that of unlisted banks. The results show that there is a significant direct impact of oil price shocks, FDI inflows, and financial crisis on bank performance. It also finds that the bank-specific factors, macroeconomic factors and financial structure indicators are significant determinants of bank performance. In terms of theories, the study finds evidence to support the moral hazard theory, competition-stability theory, defensive expansion theory and traditional intem1ediation theory (except Bahraini banks). The results are also robust when controlling for the Arab Spring transition period as well as when using alternative risk and bank competition measures. The results show that Arab Spring increases bank risk. The findings of this study have major policy implications. Gulf authorities need to enhance bank protection against risk by improving the application of Basel III especially during the crisis period like the Arab Spring. Gulf Banks also need to track the changes in oil prices as this also have impact on bank performance. There is a need for some ease of restrictions on the entry of foreign banks in the domestic market in the Gulf countries (except for Bahrain) as it can enhance bank performance.